School Drop-out and Push-out Factors in Brazil : The Role of Early Parenthood, Child Labor, and Poverty - Rute Cardoso, Ana (World Bank, Washington, DC, 2012)
This paper aims to identify the major drop-out and push-out factors that lead to school abandonment in an urban surrounding-the shantytowns of Fortaleza, Northeast Brazil. The authors use an extensive survey addressing risk factors faced by the population in these neighborhoods, which cover both in-school and out-of-school youth of both genders. They focus on the role of early parenthood, child labor, and poverty in pushing teenagers out of school. The potential endogeneity of some of the determinants is dealt with in the empirical analysis. The authors take advantage of the rich set of variables available and apply an instrumental variables approach. Early parenthood is instrumented with the age declared by the youngsters as the ideal age to start having sexual relationships. Work is instrumented using the declared reservation wage (minimum salary acceptable to work). Results indicate that early parenthood has a strong impact of driving teenagers out of school. Extreme poverty is another factor lowering school attendance, as children who have suffered hunger at some point in their lives are less likely to attend school. In this particular urban context, working does not necessarily have a detrimental effect on school attendance, which could be linked to the fact that dropping out of school leads most often to inactivity and not to work.